A guide to prospective meta-analysis. (9th October 2019) - Seidler, Anna Lene; Hunter, Kylie E; Cheyne, Saskia; Ghersi, Davina; Berlin, Jesse A; Askie, Lisa
Abstract : In a prospective meta-analysis (PMA), study selection criteria, hypotheses, and analyses are specified before the results of the studies related to the PMA research question are known, reducing many of the problems associated with a traditional (retrospective) meta-analysis. PMAs have many advantages: they can help reduce research waste and bias, and they are adaptive, efficient, and collaborative. Despite an increase in the number of health research articles labelled as PMAs, the methodology remains rare, novel, and often misunderstood. This paper provides detailed guidance on how to address the key elements for conducting a high quality PMA with a case study to illustrate each step.